The relationship between duration suffering diabetes mellitus and hearing threshold based on audiometric examination - Bambang Udji Djoko Rianto; Heri Puryanto; Kartono Sudarman (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Background: Chronic hyperglycemia is associated with a long term damage, dysfunction or failure of several organs, which is a degenerative disorder caused by persistent hyperglycemia. Complications also can cause interference with the threshold of hearing. These degenerative changes include atrophy of axons, demyelinization, and loss of nerve fibers.Objective: This study aimed to determine the relationship between long suffering diabetes mellitus and hearing thresholds based on its frequency. Methods: This study was a cross sectional design on patients with diabetes mellitus in the Internal Medicine Clinic and Otorhinolaryngology Department Dr. Sardjito General Hospital Yogyakarta from early November 2010 until the end of June 2011. Inclusion criterion were: 1) >50 years old 2) normal physical ENT examination, 3) all DM types, 4) Sensorineural (Perceptive) Hearing Loss, 5) Right and left ear gap audiogram less than 15dB, and 6) agreed to participate. Mean difference such as age and duration of DM were assessed by using independent t test and Mann Whitney test. Distribution of sex and educational level were assessed by using Chi square test and Fisher's Exact test. Correlation between duration suffering diabetes mellitus and hearing threshold was assessed by the Spearman and Pearson method. Results: Subjects participated in this research were 25 (41.7%) men and 35 (58.3%) women. Result of this study showed that there were correlation between long suffering DM and hearing thresholds at 2000Hz : (r=0.459, p=0.097), 4000Hz (r=0.4966, p=0.098), and 6000Hz (r=0.757, p=0.422), respectively.Conclusion: It is can be concluded that there is a positive correlation between long suffering DM and hearing threshold, especially after 6 years.